Anticancer Activity and Mechanism of Xanthohumol: A Prenylated Flavonoid From Hops (Humulus lupulus L.) - Jiang, Chuan-Hao; Sun, Tao-Li; Xiang, Da-Xiong; Wei, Shan-Shan; Li, Wen-Qun (Frontiers in Pharmacology, 2018)
It has been observed that many phytochemicals, frequently present in foods or beverages, show potent chemo-preventive or therapeutic properties that selectively affect cancer cells. Numerous studies have demonstrated the anticancer activity of Xanthohumol (Xn), a prenylated flavonoid isolated from Hops (Humulus lupulus L.), with a concentration up to 0.96 mg/L in beer. This review aims to summarize the existing studies focusing on the anticancer activity of Xn and its effects on key signaling molecules. Furthermore, the limitations of current studies and challenges for the clinical use of Xn are discussed.